THE RELATIONSHIP BETWEEN THE UNDERSTANDING OF INDONESIAN NATIONAL HISTORY, HISTORY LEARNING INTEREST, AND HISTORY AWARENESS AND THE NATIONALISM ATTITUDE. - Cintatia Salsabila; Aman Aman (ISTORIA: Jurnal Pendidikan dan Sejarah, 2018)
ABSTRACTThis study aimed to find out the relationship between the understanding of Indonesian national history, the history learning interest, the relationship between the history awareness and the nationalism attitude. Tests of analysis assumptions consisted of tests of normality, linearity, and multicollinearity. The hypotheses were tested using Pearson’s product moment correlation and multiple correlation with relative and effective contributions. The results of the study show that: (1) there is a significant positive relationship between the understanding of Indonesian national history and the nationalism attitude, (2) there is a significant positive relationship between the history learning interest and the nationalism attitude, (3) there is a significant positive relationship between the history awareness and the nationalism attitude, (4) there is a significant positive relationship between the understanding of Indonesian national history, history learning interest, and history awareness as an aggregate and the nationalism attitude. Keyword: understanding of Indonesian national history, history learning interest, history awareness, nationalism attitude